Association Study of Fecundity Gene BMP 15 with Prolificacy in Surti Goats under Farm and Field Condition of South Gujarat Region - Dangar, Nikhil S.; Pandya, Gaurav M.; Ramani, Umed V.; Kharadi, Vishnu B.; Brahmkshtri, B. P. (Indian Journal of Veterinary Sciences and Biotechnology, 2022)
The Surti is a dual-purpose goat breed of Gujarat. The bone morphogenetic protein 15 (BMP15), a gene of transforming growth factor-beta  (TGF-β) superfamily ligands, plays a role in ovulation and litter size. Mutation in the Exon-2 region of BMP15 gene with base size 575 bp  increases litter size. Based on the known mutation information in goat and sheep PCR primers were designed to screen polymorphism  in total 100 Surti goats, 50 Surti goats from University farm and 50 Surti goats from field units of the Southern part of Gujarat. Two  polymorphic sites were found during the study, one at 500 bp and another at 400 bp. Based on this polymorphism, three genotypes  were denoted as AA, AB, and AC for a wild or non-polymorphic region of 575 bp, polymorphic region at 500 bp, and polymorphic region  at 400 bp, respectively. The AA, AB, and AC genotypic frequency was 0.58, 0.29, and 0.13 with average kidding rate 3.01 ± 0.09, 4.65 ±  0.32 and 2.84 ± 0.24, respectively. Polymorphic region of BMP15 gene at 500 bp (AB genotype) might be used as marker genotype for  higher kidding rate at early age selection of female Surti goat.
Keywords: BMP15; Fecundity gene; Polymorphism; Prolificacy; Surti goat